The nature of the semantic/episodic memory distinction: A missing piece of the "working through" process. (2015) - Klein, Stanley B.; Markowitsch, Hans J.
Abstract: The relations between the semantic and episodic-autobiographical memory systems are more complex than described in the target article. We argue that understanding the noetic/autonoetic distinction provides critical insights into the foundation of the delineation between the two memory systems. Clarity with respect to the criteria for classification of these two systems, and the evolving conceptualization of episodic memory, can further neuroscientifically informed therapeutic approaches.